2015
DOI: 10.1104/pp.15.01108
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of plant metabolism: genetic mechanisms, interpretive caveats, evolutionary and mechanistic insights.

Abstract: Combining quantitative genetics studies with metabolomics/metabolic profiling platforms, genomics, and transcriptomics is creating significant progress in identifying the causal genes controlling natural variation in metabolite accumulations and profiles. In this review, we discuss key mechanistic and evolutionary insights that are arising from these studies. This includes the potential role of transport and other processes in leading to a separation of the site of mechanistic causation and metabolic consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 133 publications
(238 reference statements)
1
54
0
1
Order By: Relevance
“…Recently, the naturally occurring metabolic diversity within species and the underlying genetic determinants have attracted increasing research interests (Luo, ). Studies with natural or artificial populations in several species discovered that plant metabolism is moderately inheritable and shows polygenic inheritance (Chen et al ., ; Alseekh et al ., ; Soltis and Kliebenstein, ). Metabolites displayed high heritability and constant diversity within experimental populations, making the metabolome of plants an ideal target trait for population genetics studies.…”
Section: Deciphering the Genetic Bases Of Metabolic Diversity With Mgwasmentioning
confidence: 99%
“…Recently, the naturally occurring metabolic diversity within species and the underlying genetic determinants have attracted increasing research interests (Luo, ). Studies with natural or artificial populations in several species discovered that plant metabolism is moderately inheritable and shows polygenic inheritance (Chen et al ., ; Alseekh et al ., ; Soltis and Kliebenstein, ). Metabolites displayed high heritability and constant diversity within experimental populations, making the metabolome of plants an ideal target trait for population genetics studies.…”
Section: Deciphering the Genetic Bases Of Metabolic Diversity With Mgwasmentioning
confidence: 99%
“…Plants are renowned for their metabolic flexibility to generate many thousands of specialized metabolites that are non-uniformly distributed among discrete phylogenetic clades (Schilmiller et al, 2012a;Soltis and Kliebenstein, 2015). Because of their sessile lifestyles, it has been suggested that plants have developed this metabolic diversity to enable a biochemical response to environmental stimuli, often exploiting the language of low molecular weight chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis can aid in the development of standardization methods for understanding natural variation and/or various environmental conditions regarding plant growth (Kusano et al 2007b;Meyer et al 2007;Sato and Yanagisawa 2014;Soltis and Kliebenstein 2015;Sotelo-Silveira et al 2015;Sulpice et al 2009;Tamura et al 2018). According to recent studies of plant metabolic processes, metabolic profiling has shown a close link between biomass accumulation and metabolites, as both negative and positive correlations (Meyer et al 2007;Sulpice et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on analyzing natural variation under limited growth conditions or on an accession under various growth conditions (Meyer et al 2007;Sato and Yanagisawa 2014;Seaton et al 2018;Sotelo-Silveira et al 2015;Weckwerth et al 2004). Therefore, expanding research to understand fully functional systems is required (Soltis and Kliebenstein 2015). Here, our comprehensive study investigated the correlation of growth response and metabolite profiling among two Arabidopsis accessions and their F 1 hybrid under short-day conditions (SD) (12 h light, 12 h dark) and long-day conditions (LD) (16 h light, 8 h dark), with or without exogenous Suc.…”
Section: Introductionmentioning
confidence: 99%